2023
DOI: 10.1007/s12197-023-09629-8
|View full text |Cite
|
Sign up to set email alerts
|

Do artificial neural networks provide improved volatility forecasts: Evidence from Asian markets

Abstract: This paper enters the ongoing volatility forecasting debate by examining the ability of a wide range of Machine Learning methods (ML), and specifically Artificial Neural Network (ANN) models. The ANN models are compared against traditional econometric models for ten Asian markets using daily data for the time period from 12 September 1994 to 05 March 2018. The empirical results indicate that ML algorithms, across the range of countries, can better approximate dependencies compared to traditional benchmark mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…On one hand, a plethora of studies have shown that non-linear models, especially the EGARCH model, outperformed the linear counterparts in capturing and predicting the conditional variance across short-and long-term horizons (Lin 2018 (Ge et al 2023). These investigations have frequently revealed the superior predictive performance of deep learning architectures in capturing intricate long-range dependencies, often surpassing the performance of classical approaches in volatility forecasting in financial markets (Sahiner et al 2023). Moreover, the integration of deep learning algorithms such as LSTM and GRU with sentiment data has yielded remarkable advancements, showcasing substantial improvements over GARCH models (Yu et al 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On one hand, a plethora of studies have shown that non-linear models, especially the EGARCH model, outperformed the linear counterparts in capturing and predicting the conditional variance across short-and long-term horizons (Lin 2018 (Ge et al 2023). These investigations have frequently revealed the superior predictive performance of deep learning architectures in capturing intricate long-range dependencies, often surpassing the performance of classical approaches in volatility forecasting in financial markets (Sahiner et al 2023). Moreover, the integration of deep learning algorithms such as LSTM and GRU with sentiment data has yielded remarkable advancements, showcasing substantial improvements over GARCH models (Yu et al 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In finance neural networks are used in the study of financial series (Krollner et al, 2010;Zhang et al, 2023), stock prices (Bodart & Candelon, 2009;Niu et al, 2023), stock market indices (Radomska, 2021;Alkhoshi & Belkasim, 2018;Kumar & Murugan, 2013;Moghaddam et al, 2016;Song & Choi, 2023;Bhandari et al, 2022;Al-Akashi, 2022), forecasting volatility of many financial variables (Donaldson & Kamstra, 1996a, b;Salchenberger et al, 1992;Kristjanpoller et al, 2014;Ramos-Pérez et al, 2019;Liu et al, 2017;Hamid & Iqbal, 2004;Sahiner et al, 2021). For example, volatility analysis of the S&P 500 index using the LTSM40 network was conducted (Xiong et al, 2016).…”
Section: Introductionmentioning
confidence: 99%